One bad turn deserves another: How terrorism sustains the addiction to capital flight in Africa - Simplice Asongu; Rexon T. Nting; Evans Osabuohien (African Governance and Development Institute (AGDI), 2019)
This inquiry assess es if terrorism sustains the capital flight trap and whether the relationship is affected b y varying the levels of governance and globalisation. The empirical evidence is based on interactive Generalised Method of Moments with data from 37 African countries for the period 1996-2010. The followings are established. (1) Evidence of a capital flight trap is apparent because past values of capital flight have a positive effect on future values of capital flight. (2) Terrorism sustains the positive effect of the capital flight trap on capital flight. (3) For the most part (especially with regard to political governance), terrorism sustains the addiction to capital flight in above-median governance sub-samples. Policy implications are discussed.
Keywords: C50; D74; F23; N40; O55; 330; Capital flight; terrorism; Africa